Antidiabetic Potential of Ficus glomerata Roots with a Special Emphasis on Estimation of Bioactive Compounds by a Novel Validated HPTLC Technique - Upadhye, Mohini; Deokate, Uday; Pujari, Rohini; Phanse, Mohini (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: The data presented in this article for Ficus glomerata Linn. belonging to family Moraceace which is commonly found all over India. This study aimed towards the development and validation of high-performance thin-layer chromatography (HPTLC) method for simultaneous estimation of lupeol and quercetin from Ficus glomerata and correlate with its antidiabetic potential. Methods: The various fractions of ethanolic extract of Ficus glomerata root were prepared. The HPTLC analysis of quercetin and lupeol which are the important phytoconstituents responsible for various pharmacological actions was carried out at 525 nm. ICH guidelines were followed to validate this method for accuracy, precision and repeatability. Results: The linearity range of quercetin and lupeol were obtained as 400-2400 ng/spot and 1000- 5000 ng/spot respectively. Percent drug content was highest in diethyl ether fraction (quercetin 2531.8 ng and lupeol 1400 ng). The limit of detection value (LOD) obtained for quercetin and lupeol was 3.0793 and 3.1645 ng and the limit of quantification (LOQ) was 9.3314 and 9.5895 ng respectively. This method developed was accurate, precise and simple has shown higher resolution from other phytoconstituents present in the fractions. The method can be very effectively applied for analyzing the quality of herbal material and formulations containing Ficus glomerata. Antidiabetic activity of various fractions of ethanolic extract of Ficus glomerata roots was studied on alloxan-induced diabetic rats. Treatment with fractions was continued for 11 days. The effect of the fractions on glucose was analyzed. Diabetic rats treated with diethyl ether fraction exhibited a significant (p<0.05) decrease in glucose levels, indicating the potential use of Ficus glomerata in diabetes mellitus. Conclusion: As per the ICH guidelines, the HPTLC method used for simultaneous estimation of lupeol and quercetin was accurate, precise and specific. The method used for phytochemical standardization of various fractions of ethanolic extract of the roots of Ficus glomerata and correlated with its antidiabetic activity.
Keywords: Ficus glomerata; HPTLC; Lupeol; Quercetin; Alloxan; Antidiabetic activity